Das sakrale Bild von Schuld, Unschuld und Sühne - Kocher, Gernot (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
Guilt and innocence can be viewed from both the secular and the sacred side. Modern law is no longer aware of this double-sidedness, but until the legal world of the 18th century, which was determined by natural law, this two-sidedness was represented in many legal sources in the form of a combination of image and text as an opening for the sacred side, so to speak, followed by the legal text for the secular dimension. In my overview, I will present seven examples of this rich source material of European legal culture, which I will interpret according to the scientific method of legal iconography.